Differences in leaf nutrients and developmental instability in relation to induced resistance to a gall midge - Santos, Jean Carlos; Alves-Silva, Estevão; Cornelissen, Tatiana G.; Fernandes, Geraldo Wilson (Arthropod-plant interactions, 2017)
The hypersensitive response is an important form of plant-induced defence against galling insects and can imply changes in leaf nutrients, especially nitrogen and carbon, which are important for both gall survivorship and leaf development. We hypothesised that the hypersensitive response also causes leaf stress, which can be measured using leaf fluctuating asymmetry. This method evaluates deviations from leaf symmetry and is used to assess the health of plant populations, given that stressful conditions are positively related to levels of fluctuating asymmetry. In the current study, we investigated whether the hypersensitive response of Bauhinia brevipes (Fabaceae) to gall induction by Schizomyia macrocapillata (Cecidomyiidae) was related to differences in leaf nutrients (nitrogen and organic carbon) and/or levels of fluctuating asymmetry. More than 85 % of gall midges perished due to hypersensitive reactions. Fluctuating asymmetry was positively related to the hypersensitive response, and, consequently, this provides evidence that an induced response against herbivores increases plant stress. The concentration of nitrogen was negatively related to the hypersensitive response, indicating that leaves with increased induced defence tend to have low nitrogen levels, which could affect gall development and survival. Organic carbon was related neither to the hypersensitive response nor to fluctuating asymmetry. Galls are known to affect negatively plant development, and here we show that an induced defence against galls is related to differences in plant nitrogen and developmental stability.